2007
DOI: 10.1159/000101482
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Alterations during Hemodialysis: The Role of Dialysate Calcium

Abstract: Background/Aims: We investigated the way dialysate calcium (dCa) level can influence arterial stiffness (AS), measured by stiffness index (SI), a surrogate of pulse wave velocity, and reflection index (RI), a measure of the amount of pulse wave reflection, derived by digital volume pulse (DVP). Methods: Fourteen hemodialysis (HD) patients underwent two consecutive midweek 4-hour HD treatments in randomized order with a low dCa concentration of 1.25 mmol/l (LdCa) and a high dCa concentration of 1.75 mmol/l (HdC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
(38 reference statements)
1
15
0
4
Order By: Relevance
“…This was supported by another study reporting increased pulse wave velocity using a 1.75 mmol/l dialysate calcium compared to 1.25 mmol/l [5]. The question arises as to whether these effects are simply due to temporary changes in calcium flux during dialysis affecting vascular reactivity, since higher dialysate calcium concentrations lead to a net influx of calcium during dialysis [19], and so reduce the incidence of intradialytic hypotension compared to lower concentrations [20].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This was supported by another study reporting increased pulse wave velocity using a 1.75 mmol/l dialysate calcium compared to 1.25 mmol/l [5]. The question arises as to whether these effects are simply due to temporary changes in calcium flux during dialysis affecting vascular reactivity, since higher dialysate calcium concentrations lead to a net influx of calcium during dialysis [19], and so reduce the incidence of intradialytic hypotension compared to lower concentrations [20].…”
Section: Discussionsupporting
confidence: 54%
“…Increased aortic stiffness and the associated elevated pulse pressure in central arteries has been shown to be a strong and independent predictor of cardiovascular events in both the general population and also patients with chronic kidney disease [3]. Several small studies have reported that pulse wave velocity can increase following a single haemodialysis treatment when using a higher dialysate calcium concentration compared to a lower concentration [4,5]. Dialysing against higher dialysate calcium concentrations leads to greater prevalence of hypercalcaemia [6], and other small studies have reported that pulse wave velocity increases over time in both haemodialysis [7-9] and peritoneal dialysis patients [10] dialysed using higher dialysate calcium concentrations than lower.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to our data, except that we assessed central PWV, not brachial ankle PWV. Although ba-PWV is used as a convenient and accurate method to assess central arterial stiffness [10], unlike hf-PWV, ba-PWV includes peripheral stiffness with the measurements of peripheral artery velocity [17]. Generally, the correlation between central and peripheral PWV is not definite, suggesting that arterial stiffening does not occur equally, especially in patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have examined the complex relationships among serum calcium levels, the degree of vascular calcification, and arterial stiffness in patients with ESRD, and low calcium dialysate has been reported to reduce serum calcium levels, which is helpful in improving arterial stiffness [10,11]. However, these studies were relatively short-term trials and did not demonstrate serial changes in arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in patients with mild primary hyperparathyroidism have shown impaired indices of vasodilatation [62,63]. In patients undergoing hemodialysis, the induction of mild hypercalcemia, through use of a high-calcium dialysate, results in acute increases in arterial stiffness assessed by digital photoplethysmography [64]. Supportive data comes from studies of normal volunteers in whom increases in serum ionized calcium of 0.3 mmol/L increase systolic blood pressure (mean±SD, 114±13-121±10 mmHg; P<0.05) and result in dose-related impairment in endothelial vasodilator function [65].…”
Section: Mechanisms Of Calcium Supplement Effect On Vascular Diseasementioning
confidence: 99%